2007
DOI: 10.1101/lm.477007
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal regulation of context-dependent neuronal activity in the lateral amygdala

Abstract: Pavlovian fear conditioning is a robust and enduring form of emotional learning that provides an ideal model system for studying contextual regulation of memory retrieval. After extinction the expression of fear conditional responses (CRs) is context-specific: A conditional stimulus (CS) elicits greater conditional responding outside compared with inside the extinction context. Dorsal hippocampal inactivation with muscimol attenuates context-specific CR expression. We have previously shown that CS-elicited spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 73 publications
3
108
2
Order By: Relevance
“…In this study, we inactivated the dorsal hippocampus using muscimol, a GABA receptor type A agonist that has been used previously to inhibit hippocampal activity (Moser and Moser 1998;Holt and Maren 1999;Maren and Hobin 2007). Muscimol was injected into the dorsal hippocampus through guide cannulae implanted in the mouse brain by stereotaxic surgery.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we inactivated the dorsal hippocampus using muscimol, a GABA receptor type A agonist that has been used previously to inhibit hippocampal activity (Moser and Moser 1998;Holt and Maren 1999;Maren and Hobin 2007). Muscimol was injected into the dorsal hippocampus through guide cannulae implanted in the mouse brain by stereotaxic surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is that the hippocampus gates fear expression directly through projections to the LA. A recent study showed that the context-specific modulation of both fear expression and CS-evoked activity in the LA (greater responding in the non-extinction context than in the extinction context) depends on the hippocampus (Maren and Hobin, 2007). Although clarification of the precise circuitry requires further investigation, there is strong evidence that the hippocampus, through communication with the vmPFC and the amygdala, regulates the contextual modulation of fear expression during extinction retrieval.…”
Section: Extinctionmentioning
confidence: 99%
“…Frodl et al (2002) found reduced hippocampal volume in male participants with first-ever depressive episode, suggesting that hippocampal degeneration precedes the onset of depression. Structures, such as the prefrontal cortex, the amygdala, and nucleus accumbens receive inputs from the hippocampus, thus providing a possibility for altered hippocampal function to affect emotionality (Maren and Hobin 2007;O'Donnell and Grace 1995). A recent prospective study, however, disagrees with this theory, as they reported that depression might lead to a faster rate of hippocampal volume decline, but they found no evidence for smaller hippocampal volume to precede the development of depression (den Heijer et al 2011).…”
Section: Discussionmentioning
confidence: 70%